O POEMA CLÁSSICO NA EDUCAÇÃO ESCOLAR À LUZ DA PEDAGOGIA HISTÓRICO-CRÍTICA - Figueiredo, Luana Martins (2020)
Based on the historical-critical pedagogy, this research addresses a theoreticalconceptual study of classic poem, comprehended as a resource for an aesthetic-literary teaching that contributes to human emancipation. We relate the emergence of poem to the